2024
DOI: 10.3390/molecules29051000
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin, a Flavonoid with Great Pharmacological Capacity

Eber Josue Carrillo-Martinez,
Flor Yohana Flores-Hernández,
Adriana María Salazar-Montes
et al.

Abstract: Quercetin is a flavonoid with a low molecular weight that belongs to the human diet’s phenolic phytochemicals and nonenergy constituents. Quercetin has a potent antioxidant capacity, being able to capture reactive oxygen species (ROS), reactive nitrogen species (RNS), and reactive chlorine species (ROC), which act as reducing agents by chelating transition-metal ions. Its structure has five functional hydroxyl groups, which work as electron donors and are responsible for capturing free radicals. In addition to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…Quercetin, a flavonoid abundant in fruits and vegetables, is known for its potent antioxidant properties, attributed to its ability to donate electrons and scavenge free. Numerous studies have highlighted quercetin’s role in protecting against oxidative stress-induced damage and its potential therapeutic benefits in neurodegenerative disease radicals [ 82 ]. Similarly, biotin, an essential B vitamin, has been shown to enhance antioxidant defences and promote mitochondrial function, thereby mitigating oxidative damage [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, a flavonoid abundant in fruits and vegetables, is known for its potent antioxidant properties, attributed to its ability to donate electrons and scavenge free. Numerous studies have highlighted quercetin’s role in protecting against oxidative stress-induced damage and its potential therapeutic benefits in neurodegenerative disease radicals [ 82 ]. Similarly, biotin, an essential B vitamin, has been shown to enhance antioxidant defences and promote mitochondrial function, thereby mitigating oxidative damage [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of ant nest potential using the Structural Activity Relationship (SAR) approach with pass online 26 Based on SAR analysis, it has been identified that bioactives present in apple peel exhibit the highest potential as Free Radical Scavengers (0.754). Additionally, these bioactives show potential as Lipid Peroxidase Inhibitors (0.671), Antihypercholesterolemics (0.577), and Lipid Metabolism Regulators (0.468) (see Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is a major representative of the flavonoid family that can be found in various vegetables and fruits. Quercetin plays an important role in treating numerous diseases by exerting anti-inflammatory, antioxidant, anti-neovascular, and neuroprotective effects [ 119 , 120 , 121 ]. In diabetic rats, quercetin supplementation increased neurotrophic factors and inhibited cytochrome c and caspase-3, thereby protecting the retina from oxidative stress and apoptosis.…”
Section: Natural Products In the Treatment Of Diabetic Retinopathymentioning
confidence: 99%